2008
DOI: 10.1021/je700632z
|View full text |Cite
|
Sign up to set email alerts
|

Viscosities of Liquid Fluorocompounds

Abstract: In spite of their interest, viscosities of fluorocarbon compounds are scarce, and the available data are unreliable and of poor accuracy. In this work, viscosity measurements of linear, cyclic, aromatic, and R-substituted perfluorocarbons were carried out in the temperature range between (298.15 and 318.15) K using an Ubbelohde viscometer. The experimental results show that fluorinated compounds present viscosities considerably higher than their hydrocarbon homologues as expected. The viscosities increase from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…6. Freire et al 32 reported that perfluoroalkane has a higher viscosity than its alkane homologues. In general, the perfluoroalkyl group is thought to be rigid when compared with the normal alkyl group.…”
Section: Comparison Of Intramolecular Rotational Movements Of Sf-acidmentioning
confidence: 99%
“…6. Freire et al 32 reported that perfluoroalkane has a higher viscosity than its alkane homologues. In general, the perfluoroalkyl group is thought to be rigid when compared with the normal alkyl group.…”
Section: Comparison Of Intramolecular Rotational Movements Of Sf-acidmentioning
confidence: 99%
“…Experimental data on the viscosity of fluorocarbons are rather scarce in literature. In perhaps the only study to date, Freire et al 65 have measured the viscosity of several linear (F6 to F9), cyclic, aromatic, and R-substituted perfluorocarbons, over a relatively limited range of temperature.…”
Section: Articlementioning
confidence: 99%
“…By contrast, the carbon-fluorine bond creates strong intramolecular forces [1,2]. As a result, PFCs and FCs present unusual and interesting properties, as for example, large solubility for gases, exceptional chemical and biological inertness, excellent spreading characteristics, low surface tension and refractive index, density higher than water, and high isothermal compressibility [3][4][5][6][7]. Due to their intrinsic properties, PFCs and FCs are commonly used in the most diverse commercial and industrial applications ranging from cleaning solvents, fire suppression agents, heat transfer fluids, surfactants in supercritical solvents, in uranium enrichment, and as aerosol solvents [8].…”
Section: Introductionmentioning
confidence: 99%